Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Let's solve each expression step by step to find their respective values.
1. Evaluate [tex]\( f(2) \)[/tex]:
[tex]\[ f(x) = 3x^2 + 2 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 2 = 3(4) + 2 = 12 + 2 = 14 \][/tex]
2. Evaluate [tex]\( g(3) \)[/tex]:
[tex]\[ g(x) = 4x^2 + 2x - 1 \][/tex]
Substitute [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = 4(3)^2 + 2(3) - 1 = 4(9) + 6 - 1 = 36 + 6 - 1 = 41 \][/tex]
3. Evaluate [tex]\( h(4) \)[/tex]:
[tex]\[ h(x) = 2x - 3 \][/tex]
Substitute [tex]\( x = 4 \)[/tex]:
[tex]\[ h(4) = 2(4) - 3 = 8 - 3 = 5 \][/tex]
4. Evaluate [tex]\( f(1) + g(1) \)[/tex]:
[tex]\[ f(x) = 3x^2 + 2,\quad g(x) = 4x^2 + 2x - 1 \][/tex]
Substitute [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 3(1)^2 + 2 = 3(1) + 2 = 3 + 2 = 5 \][/tex]
[tex]\[ g(1) = 4(1)^2 + 2(1) - 1 = 4(1) + 2(1) - 1 = 4 + 2 - 1 = 5 \][/tex]
[tex]\[ f(1) + g(1) = 5 + 5 = 10 \][/tex]
5. Evaluate [tex]\( h(2) + f(2) \)[/tex]:
[tex]\[ h(x) = 2x - 3,\quad f(x) = 3x^2 + 2 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ h(2) = 2(2) - 3 = 4 - 3 = 1 \][/tex]
[tex]\[ f(2) = 3(2)^2 + 2 = 3(4) + 2 = 12 + 2 = 14 \][/tex]
[tex]\[ h(2) + f(2) = 1 + 14 = 15 \][/tex]
Finally, let's match the expressions with their results:
[tex]\[ \begin{array}{l} f(2) = 14 \\ g(3) = 41 \\ h(4) = 5 \\ f(1) + g(1) = 10 \\ h(2) + f(2) = 15 \\ \end{array} \][/tex]
Thus, the correct answers to the given functions are:
[tex]\[ \begin{array}{l} f(2) = 14 \\ g(3) = 41 \\ h(4) = 5 \\ f(1) + g(1) = 10 \\ h(2) + f(2) = 15 \\ \end{array} \][/tex]
1. Evaluate [tex]\( f(2) \)[/tex]:
[tex]\[ f(x) = 3x^2 + 2 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 3(2)^2 + 2 = 3(4) + 2 = 12 + 2 = 14 \][/tex]
2. Evaluate [tex]\( g(3) \)[/tex]:
[tex]\[ g(x) = 4x^2 + 2x - 1 \][/tex]
Substitute [tex]\( x = 3 \)[/tex]:
[tex]\[ g(3) = 4(3)^2 + 2(3) - 1 = 4(9) + 6 - 1 = 36 + 6 - 1 = 41 \][/tex]
3. Evaluate [tex]\( h(4) \)[/tex]:
[tex]\[ h(x) = 2x - 3 \][/tex]
Substitute [tex]\( x = 4 \)[/tex]:
[tex]\[ h(4) = 2(4) - 3 = 8 - 3 = 5 \][/tex]
4. Evaluate [tex]\( f(1) + g(1) \)[/tex]:
[tex]\[ f(x) = 3x^2 + 2,\quad g(x) = 4x^2 + 2x - 1 \][/tex]
Substitute [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 3(1)^2 + 2 = 3(1) + 2 = 3 + 2 = 5 \][/tex]
[tex]\[ g(1) = 4(1)^2 + 2(1) - 1 = 4(1) + 2(1) - 1 = 4 + 2 - 1 = 5 \][/tex]
[tex]\[ f(1) + g(1) = 5 + 5 = 10 \][/tex]
5. Evaluate [tex]\( h(2) + f(2) \)[/tex]:
[tex]\[ h(x) = 2x - 3,\quad f(x) = 3x^2 + 2 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ h(2) = 2(2) - 3 = 4 - 3 = 1 \][/tex]
[tex]\[ f(2) = 3(2)^2 + 2 = 3(4) + 2 = 12 + 2 = 14 \][/tex]
[tex]\[ h(2) + f(2) = 1 + 14 = 15 \][/tex]
Finally, let's match the expressions with their results:
[tex]\[ \begin{array}{l} f(2) = 14 \\ g(3) = 41 \\ h(4) = 5 \\ f(1) + g(1) = 10 \\ h(2) + f(2) = 15 \\ \end{array} \][/tex]
Thus, the correct answers to the given functions are:
[tex]\[ \begin{array}{l} f(2) = 14 \\ g(3) = 41 \\ h(4) = 5 \\ f(1) + g(1) = 10 \\ h(2) + f(2) = 15 \\ \end{array} \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.